Comparative Endocrinology of Aging and Longevity Regulation - Allard, John; Duan, Cunming (Frontiers in Endocrinology, 2011)
Hormones regulate growth, development, metabolism, and other complex processes in multicellular animals. For many years it has been suggested that hormones may also influence the rate of the aging process. Aging is a multifactorial process that causes biological systems to break down and cease to function in adult organisms as time passes, eventually leading to death. The exact underlying causes of the aging process remain a topic for debate, and clues that may shed light on these causes are eagerly sought after. In the last two decades, gene mutations that result in delayed aging and extended longevity have been discovered, and many of the affected genes have been components of endocrine signaling pathways. In this review we summarize the current knowledge on the roles of endocrine signaling in the regulation of aging and longevity in various animals. We begin by discussing the notion that conserved systems, including endocrine signaling pathways, “regulate” the aging process. Findings from the major model organisms: worms, flies and rodents, are then outlined. Unique lessons from studies of non-traditional models: bees, salmon and naked mole rats, are also discussed. Finally, we summarize the endocrinology of aging in humans, including changes in hormone levels with age, and the involvement of hormones in aging-related diseases. The most well studied and widely conserved endocrine pathway that affects aging is the insulin/insulin-like growth factor system. Mutations in genes of this pathway increase the lifespan of worms, flies, and mice. Population genetic evidence also suggests this pathway’s involvement in human aging. Other hormones including steroids have been linked to aging only in a subset of the models studied. Because of the value of comparative studies, it is suggested that the aging field could benefit from adoption of additional model organisms.